FDI Spillover Channel and its Effect on Innovation - Darfo-Oduro, Raymond Kwame Adane; Stejskal, Jan (Academic Conferences International Limited, 2022)
In an increasingly globalized environment, one of the important aspects for knowledge development and usage has been the advantage of benefiting from knowledge spillover across international boundaries. The knowledge literature recognizes the importance of the combining internal and external knowledge in the innovation process. Knowledge spillover from abroad is an important channel of external knowledge needed to complement the innovation activities in the domestic economies of countries. However, the complementarities of external knowledge and domestic innovation activities also remains a thorny issue that remain unresolved in the knowledge literature. On one hand, there is a believe that combinatorial efforts of domestic and foreign knowledge activities are a good recipe for innovation. There are other strands of literature that are concerned that when foreign knowledge is not complementary with domestic innovation activities increased innovation may not be realized. Contrary to the widely held view of the positive impact of FDI on host economies, the literature shows a rather complex relationship between FDI and economic outcomes in V4 countries. OECD countries, being the main trading partners of V4 countries, the study therefore investigates the FDI channel for knowledge spillover from OECD countries and how such knowledge spillover complements V4 countries innovation activities to affect innovation outcomes. Data for the study is panel data on the V4 countries, spanning 2003 to 2012 which is sourced from the OECD database. The study applies panel regression analysis and controls for country and time fixed effect to determine the role of FDI knowledge spillover from OECD countries on innovation outcome in V4 countries. The findings of the study indicate that proportionate change in innovation is greater than a proportionate change in FDI knowledge spillover in the opposite direction. The results of the analysis show that knowledge spillover from FDI does not complement V4 countries’ internal R&D activities to improve innovation. FDI knowledge spillover channel is not a good complement to domestic R&D activities to enhance V4 countries’ innovation performance. It is concluded that, FDI knowledge spillover channel does not complement innovation activities to improve innovation outcome. The study provides useful practical implications and recommendations.
Přímé zahraniční investice a jejich vliv na inovace
Keywords: FDI; knowledge spillover; innovation; R&D intensity; Visegrad 4 countries; přímé zahraniční investice; přelévání znalostí; intenzita výzkumu a vývoj; země V4